Integrating Quality Assurance in the Algerian Higher Education - Saadi, Keltoum (Journal of Human Sciences, 2019)
Many universities and institutions around the world have set up different internal and external mechanisms ensuring quality and best practices. Effective quality assurance systems beyond those institutions themselves are becoming of higher priority in national strategies. As a result, many countries worldwide have set up Higher Education (HE) quality assurance agencies at the national level. Although Algeria has followed their counterparts in adopting quality assurance programmes in Higher Education, the quality assurance (QA) system is still at an infant stage and confronted by many challenges. The purpose of this paper is to furnish local and global stakeholders with detailed information regarding the development and the current status of quality assurance in the Algerian higher education sector. This paper addresses the dearth of documented information on issues of quality assurance in Algeria. In addition, it discusses examples of  QA programmes and best practices that could be emulated.